Literature Study: The Influence Of Educational Background And Work Experience On Employee Performance - Hanazka Syahla; Cecep Hermana (Primanomics : Jurnal Ekonomi & Bisnis, 2026)
This study aims to determine the effect of work experience on employee performance based on a literature review. Analyze the combined effect of educational background and work experience on employee performance. Identify supporting and inhibiting factors in the relationship between education, work experience, and employee performance. Provide a conceptual overview and recommendations regarding the equivalence of education and work experience in improving employee performance. The research method used is a library study, where researchers review previous research and then draw conclusions from the results. This study was conducted by reanalyzing previous research relevant to the research objectives and developing a deeper understanding. Based on the results of the reanalysis of three previous studies, this study shows that educational background and work experience have a significant influence on employee performance. A higher level of education positively contributes to improved cognitive abilities, technical skills, and understanding of job duties and responsibilities. This results in increased efficiency, work quality, and problem-solving abilities in the workplace.Furthermore, work experience has also been shown to have a positive relationship with employee performance. Employees with longer tenure tend to have a better understanding of systems, organizational culture, and applicable work procedures. This experience allows them to work more effectively, reduce errors, and adapt more quickly to changes or challenges in the workplace. Simultaneously, the combination of a good level of education and adequate work experience forms stronger work competencies, which ultimately contributes to increased productivity and overall performance quality. These results are in line with previous research findings which confirm that human resources with a higher educational background and extensive work experience are important assets for organizations in achieving goals and competitive advantages.